2018
DOI: 10.1042/bsr20180922
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound microbubbles mediated miR-let-7b delivery into CD133+ ovarian cancer stem cells

Abstract: Ovarian cancer stem cells (OCSCs) are considered the reason for ovarian cancer’s emergence and recurrence. Ultrasound-targetted microbubble destruction (UTMD), a non-vial, safe, and promising delivery method for miRNA, is reported to transfect cancer stem cells (CSCs). In the present study, we investigated to transfect miR-let-7b into OCSCs using UTMD. The CD133+ OCSCs, accounted for only 0.1% of ovarian cancer cell line A2780, were separated by flow cytometry, and the CSC characteristics of CD133+ OCSCs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Microbubble ultrasound contrast agent-mediated gene transfection would be an advantageous transfection method to be widely used in the future. Ultrasound microbubble-mediated miRNA delivery into CD133+ ovarian cancer stem cells and human hepatoma HepG2 cells have been reported, and the effects were found better than the single liposome, microbubble or ultrasound,18,34 which were consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Microbubble ultrasound contrast agent-mediated gene transfection would be an advantageous transfection method to be widely used in the future. Ultrasound microbubble-mediated miRNA delivery into CD133+ ovarian cancer stem cells and human hepatoma HepG2 cells have been reported, and the effects were found better than the single liposome, microbubble or ultrasound,18,34 which were consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that let‐7b inhibition increases the expression of HMGA2, 17 c‐Myc, Dicer, and Imp3 10 in ovarian cancer cells. Another study introduced let‐7b into ovarian cancer stem cells with ultrasound microbubbles, which resulted in significantly increased cell apoptosis and a decrease in the expression of CD133, a cancer stemness marker 18 . However, it is unknown whether CD133 is the direct target of let‐7b.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, UTMD technology is able to significantly facilitate the co-transmission of gemcitabine and miR-21i and thus provides a promising strategy for the effective treatment of pancreatic cancer ( 33 ). In the study of Yang et al ( 34 ), miR-let-7b was transfected into ovarian cancer stem cells by flow cytometry, and the results indicated that miR-let-7b transfection efficiency using UTMD was significantly higher. In NSCLC, the expression level of miR-767 could be successfully downregulated by miR-767 inhibitor and UTMD further enhanced the transfection efficacy of miR-767 inhibitor, while downregulation of miR-767 was indicated to inhibit the proliferation, migration and invasion of tumor cells ( 15 ).…”
Section: Discussionmentioning
confidence: 99%